12 Precision imaging of coronary atherosclerotic microcalcification using 18F-fluoride. (May 2018) - Moss, Alastair J; Adamson, Philip D; Doris, Mhairi K; Andrews, Jack; Sim, Alisia; van Beek, Edwin JR; Forsyth, Laura; Lee, Robert; Lewis, Steff; Tarvares, Adriana; Dweck, Marc R; Newby, David E
Abstract : Introduction: 18F-Fluoride is a highly sensitive positron emission tomography tracer that binds to microcalcification. When combined with computed tomography angiography (PET-CT), it enables simultaneous anatomical and metabolic imaging that non-invasively identifies high-risk plaques in coronary arteries. Uncertainty persists regarding the optimal parameter to quantify metabolic activity in coronary arteries and reliably discriminate 18F-fluoride from the surrounding myocardium. This prospective clinical study evaluates the precision of 18F-fluoride quantification. Methods: Thirty patients with multi-vessel coronary artery disease underwent serial 18F-fluoride coronary PET-CT within 2 weeks. Coronary 18F-fluoride maximum activity (SUVMAX ) was referenced to left atrial activity (TBRMAX ) to evaluate the accuracy of repeated measures. Coefficient of variance of 18F-fluoride was calculated to establish a threshold of precision measurement. Results: Twenty patients with stable coronary artery disease and ten patients with recent acute coronary syndrome. All coronary artery segments (n=171) were measured in sextuplicate with diagnostic precision of 18F-fluoride activity (coefficient of variation <15%) at values of TBRMAX >0.9. A single plaque TBRMAX >0.9 was present in 90% (n=9/10) of acute coronary syndrome patients and 60% (n=12/20) of stable coronary artery disease patients. On a per-patient level, the overall agreement for visual assessment of 18F-fluoride uptake was good (κ=0.64) and was significantly improved with the application of a quantitative threshold (κ=0.84). Conclusion: 18F-fluoride PET-CT provides a precise measurement of calcification activity in the coronary vasculature. These assessment techniques will support prospective trials of this radiotracer as a non-invasive imaging biomarker of plaque vulnerability.